2017
DOI: 10.3389/fpubh.2017.00320
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary Luteinizing Hormone Tests: Which Concentration Threshold Best Predicts Ovulation?

Abstract: ObjectiveTo study the best possible luteinizing hormone (LH) threshold to predict ovulation within the 24, 48, and 72 h.DesignObservational study.SettingMulticenter collaborative study.PatientsA total of 107 women.InterventionsWomen collected daily first morning urine for hormonal assessment and underwent serial ovarian ultrasound. This is a secondary analysis of 283 cycles.Main outcome measuresThe sensitivity, specificity, positive and negative predictive values, and positive and negative likelihood ratios we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…After all, in 1957 Wray [158: 529] observed that "[t]he practice of reporting pregnanediol outputs in mg per unit volume is contra-indicated by its great inaccuracy" and very similar comments were made a century earlier by Thudichum [159]. Despite this, the use of u A in the measurement of urinary metabolites of reproductive hormones continues [2,6,7,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Moreover, there is still confusion in the literature about u A , J A and their link to J V .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, in 1957 Wray [158: 529] observed that "[t]he practice of reporting pregnanediol outputs in mg per unit volume is contra-indicated by its great inaccuracy" and very similar comments were made a century earlier by Thudichum [159]. Despite this, the use of u A in the measurement of urinary metabolites of reproductive hormones continues [2,6,7,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Moreover, there is still confusion in the literature about u A , J A and their link to J V .…”
Section: Discussionmentioning
confidence: 99%
“…The inevitable question is whether such a difference in u A has any physiological significance. In spite of these uncertainties, reports of the use of concentration measurements to monitor reproductive hormones in urine are increasingly common and in some it is claimed that specific threshold values are associated with particular events in the cycle [2,6,7,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. In none of these cases were the data of a single cycle used by a woman to monitor her own fertility.…”
Section: The Urinary Concentration Of Analyte a (U A ) Is Just The Qumentioning
confidence: 99%
“…Intact LH surges prior to ovulation and is excreted quickly, whereas assays measuring beta LH also detect LH breakdown products that are excreted more slowly. Therefore, beta LH assays can often provide profiles with more than one surge and have peak levels occurring at a considerable time after ovulation [14][15][16][17][18] . As peak levels can occur post ovulation, even with an intact LH assay, it is more appropriate to measure the LH surge: there are a wide variety of methods for determining the surge 19 , with the most accurate method providing 1-day prediction of ovulation with maximal error of ±1 day 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, with a prospective approach, the use of home kits that detect threshold urinary LH rise to target the luteal phase has become main stream. However, a recent paper points out the inaccuracy of using these threshold LH tests by themselves to detect ovulation ( 19 ), even though, they could be utilized along with PG rise threshold in-home tests or with the peak mucus sign.…”
Section: Introductionmentioning
confidence: 99%